Mathematical Models Used for Brachytherapy Treatment Planning Dose Calculation Algorithms - Shefali Kanwar; Surbhi Gupta (مجلة بغداد للعلوم)
Brachytherapy treatment is primarily used for the certain handling kinds of cancerous tumors. Using radionuclides for the study of tumors has been studied for a very long time, but the introduction of mathematical models or radiobiological models has made treatment planning easy. Using mathematical models helps to compute the survival probabilities of irradiated tissues and cancer cells. With the expansion of using HDR-High dose rate Brachytherapy and LDR-low dose rate Brachytherapy for the treatment of cancer, it requires fractionated does treatment plan to irradiate the tumor. In this paper, authors have discussed dose calculation algorithms that are used in Brachytherapy treatment planning. Precise and less time-consuming calculations using 3D dose distribution for the patient is one of the important necessities in modern radiation oncology. For this it is required to have accurate algorithms which help in TPS. There are certain limitations with the algorithm which are used for calculating the dose. This work is done to evaluate the correctness of five algorithms that are presently employed for treatment planning, including pencil beam convolution (PBC), superposition (SP), anisotropic analytical algorithm (AAA), Monte Carlo (MC), Clarkson Method, Fast Fourier Transform, Convolution method. The algorithms used in radiotherapy treatment planning are categorized as correction‐based and model‐based.